Cover Jurnal Fitopatologi Vol. 19 No. 2, Maret 2023 - ju, Editors Jurnal Fitopatologi Indonesia; Editors Jurnal Fitopatologi Indonesia (Jurnal Fitopatologi Indonesia, 2023)
This editorial contains the front cover, editorial page, and back cover of the Jurnal Fitopatologi Indonesia Vol. 19 No. 2, March 2023